2016
DOI: 10.1007/s10995-016-2089-7
|View full text |Cite
|
Sign up to set email alerts
|

Barriers in the Uptake and Delivery of Preconception Care: Exploring the Views of Care Providers

Abstract: Objectives To examine health care professionals' views of their role and responsibilities in providing preconception care and identify barriers that affect the delivery and uptake of preconception care. Methods Twenty health care professionals who provide preconception care on a regular basis were interviewed using semistructured interviews. Results We interviewed twelve community midwives, three General Practitioners, three obstetricians, one cardiologist specialized in congenital heart diseases and one gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 24 publications
5
45
0
Order By: Relevance
“…Preparation for pregnancy and preconception care has been one recent focus 48,75,130 . Previously, the main preconception focus of health services has been on the prevention of unintended pregnancy through provision of contraception 131 . Nevertheless, in countries with high levels of primary care coverage, in which a majority of women make contact with health services at least annually, there would be scope to screen and intervene around intergenerational health risks 132 .…”
Section: Adolescence and The Next Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation for pregnancy and preconception care has been one recent focus 48,75,130 . Previously, the main preconception focus of health services has been on the prevention of unintended pregnancy through provision of contraception 131 . Nevertheless, in countries with high levels of primary care coverage, in which a majority of women make contact with health services at least annually, there would be scope to screen and intervene around intergenerational health risks 132 .…”
Section: Adolescence and The Next Generationmentioning
confidence: 99%
“…Nevertheless, in countries with high levels of primary care coverage, in which a majority of women make contact with health services at least annually, there would be scope to screen and intervene around intergenerational health risks 132 . The major barriers are the low current demand from future parents and a limited provision of more comprehensive healthcare, particularly for women at the greatest risk 131 . There is little doubt that a reorientation of service systems towards preconception would be of value 133 .…”
Section: Adolescence and The Next Generationmentioning
confidence: 99%
“…Nevertheless data are scarce about the influence of periconceptional maternal nutrition on embryonic growth. This is related to the fact that, in clinical practice, the embryonic period is often missed and to the widespread assumption that embryonic growth is the same in every pregnancy and woman. However, over the last decade new insights have revealed that first‐trimester embryonic growth differs between pregnancies and is significantly associated with periconceptional maternal characteristics, nutrition and lifestyle, including age, ethnicity, smoking and alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…HCPs such as obstetricians and gynecologists (OBGYNs) and midwives play a crucial role in implementing preventive strategies in the preconception period and are well‐placed to integrate early life risk reduction into a life course approach to health care. According to a study of Dutch obstetricians and physicians, uncertainty among HCPs about the need and effectiveness of preconception interventions appears to influence the decision to discuss preconception issues . If addressed at all, preconception care is generally discussed at the end of consultations with general practitioners, and covering all risks that could affect future pregnancies is a challenge .…”
Section: Introductionmentioning
confidence: 99%
“…The delivery of preconception services can also be influenced by the variety of risk factors requiring communication between specialties, poor organization of preconception care systems and HCPs’ views on their professional roles and responsibilities. HCPs also want to respect the patient's right to choose autonomously whether or when to become pregnant, which may sometimes be seen to present ethical barriers to discussing the issue of planning for pregnancy or reducing weight before conception …”
Section: Introductionmentioning
confidence: 99%